QCM SENSOR SENSITIVITY ANALYSIS OF SILVER ELECTRODES COATED WITH LIPID MEMBRANE OLEYL ALCOHOL TOWARD NaCl AND HCl - Ummah, Auliya Rahmatul; Tazi, Imam; Muthmainnah, Muthmainnah (Department of Physics, Maulana Malik Ibrahim State Islamic University of Malang, 2019)
One of the sensors, which is currently being developed is the QCM sensor. The QCM sensor is a sensor that utilizes the frequency change to detect a change in mass due to a test substance. The use of a QCM sensor includes other forms of electronic tongue sensor that can distinguish five basic flavours on the tongue. QCM sensor can also be varied electrodes using various lipid membranes such as electronic tongues to increase sensor sensitivity. This research aims to determine the sensitivity of the QCM sensor before and after coated with the lipid membrane to NaCl and HCl. The sensitivity of the QCM sensor to NaCl is 1.47 Hz/M for uncoated sensor and 0.63 Hz/M for coated sensor, while the sensitivity of HCl is 4.55 Hz/M for uncoated sensor and 4.93 Hz/M for coated sensor. The difference of the results is caused by the nature of ionization of the compound and the amount of concentration used. The result of the sensitivity research shows that the QCM sensor with Oleyl Alcohol lipid membrane is more sensitive to HCl than NaCl.